Camellia sinensis extract phytosomes inhibit body weight gain in Sprague-Dawley rats - Dwi Kurnia Putri; Iskandarsyah Iskandarsyah; Effionora Anwar (Universitas Ahmad Dahlan, 2020)
A phytosome is a kind of nanovesicle lipids to increase the absorption of active substances. Green tea extract was formulated into phytosome to find out its ability to inhibit weight gain. There were three formulas with thin layer hydration. Furthermore, phytosome complex formation, morphology, particle size, zeta potential, and polydispersity index, and absorption efficiency test were characterized. Phytosomes and green tea extracts were tested for absorption in vitro. A total of 25 rats were divided into five test groups, which were the normal group, placebo group, orlistat group, green tea extract group, and phytosome group. For 8 weeks they were orally induced using 10% of fructose + 2% of cholesterol, and test treatment. The best characteristics of FIII were formed complex, spherical morphology, Dv90 782.67 ± 39.7 nm, polydispersity index of 56 ± 0.11, zeta potential of -70.83 ± 1.67 mV, and adsorption efficiency of 97.77 ± 2.66 %. The test on the animals at week 8 resulted in percentage of weight gain in normal treatment of 46.47 ± 17.48%, placebo of 101.17 ± 10.37%, orlistat of 42.51 ± 25.13%, green tea extract of 92.73 ± 36.43%, and phytosomes of 45.09 ± 15.56%. Green tea extract flux was 2316.2 ± 1309.8 μg/cm2/hour, while phytosome flux was 3125.3 ± 2071.8 μg /cm2/hour. To sum up, phytosomes can inhibit weight gain and are better than to green tea extracts (p < 0.05).